Clinical researchValue of C-reactive protein and IL-6 measurements in type 1 diabetes mellitus - Fawaz, Lubna; Elwan, Amany E.; Kamel, Yasser H.; Farid, Tarek M.; Kamel, Abdelkareem; Mohamed, Waleed A. (Archives of Medical Science, 2009)
Introduction: The role of non-specific inflammation in b-cell loss in type 1 diabetes (T1DM) is unclear. In the present study, inflammatory markers were determined in patients with type 1 diabetes mellitus (T1DM) and related to conventional risk factors for cardiovascular disease. To determine the levels of high sensitive CRP (hs-CRP) and interleukin-6 (IL-6) as markers of inflammation in type I diabetes mellitus and to investigate their determinants in type 1 diabetes and their correlation with conventional risk factors for cardiovascular problems. Material and methods: Plasma hs-CRP and IL-6 were measured in 70 young patients with type 1 diabetes mellitus. Forty patients were well controlled on intensive insulin therapy (group I), while 30 patients were not controlled on in spite of intensive insulin therapy (group II). These results were compared to those of 30 age- and sex-matched healthy children. All subjects were assessed for a family history of type 2 diabetes and history of premature cardiovascular illness, presence of hypertension, body mass index (BMI), HbA1c and serum lipids, all of which are considered to be risk factors for cardiovascular problems. Results: Diabetic patients had significantly higher levels of hs-CRP and IL-6 than the non diabetic control group (p-value < 0.001, < 0.05 respectively). The uncontrolled diabetes group showed significantly higher levels of the two markers than the controlled diabetic group (p-value < 0.000). Serum levels of IL-6 correlated positively with hs-CRP (r = 0.926, p < 0.0001). Hs-CRP and IL-6 correlated positively with HbA1c, BMI, total cholesterol (p < 0.000), LDL (p < 0.0001) and triglycerides (p < 0.000), whereas HDL showed a negative correlation to both hs-CRP and IL-6 (p < 0.000). There was a significantly higher incidence of hypertension, a family history of cardiovascular disease and a family history of type 2 diabetes in the uncontrolled diabetes group (p < 0.000). Hs-CRP and IL-6 were significantly higher in patients with a family history of type 2 diabetes mellitus (p < 0.005). Conclusions: In type I diabetes there is an increase in the inflammatory markers, hs-CRP and IL-6 denoting subclinical chronic inflammation. These markers correlate significantly with conventional risk factors for vascular disease, namely hypertension, dyslipidemia, high body mass index and glycemic control. Type 1 diabetes patients with a positive family history of type 2 diabetes mellitus have higher hs-CRP and IL-6 levels indicating that they are more prone to cardiovascular complications.